The Nigerian Industrial production index - Fahm, L. A. (Lagos Nigeria, 1968)
The book provides some empirical facts on the behavior of the key sectors of the Nigerian economy so that the right type of information would be available for those interested. Secondly
bhb 24/04/2019
Arch
Keywords: Industrialisation; Nigeria